Telhado verde e sua contribuição para a redução da temperatura ambiente em construções para Cascavel/PR - Souza, Cássia Rafaela Brum (2016)
Since the second half of the nineteenth century, energy plays a key role in the gear of modern industrial society, moving numerous systems and equipment, but its overuse has caused its scarcity. Assuming that renewable energy comes from renewable resources, naturally replenished, from the sun, wind, rain, tides and geothermal energy, some can be exploited intensively, and when combined with bioclimatic architecture and energy efficiency can have adequate thermal inertia a building with adequate insulation elements, maintaining thermal comfort inside the room during times of peak temperature and solar radiation outside and thus respectively controlling excess heat. To this end this work becomes significant because it was developed in order to provide two different conditions of buildings, in which the cover is differentiating factor for withdrawals and verification of energy efficiency. The research shows the variation of the internal temperature of the environment covered by the green roof and a conventional, and their loss to the environment over the hours of the day and night as well as the influence of the green roof substrate at room temperature inside, demonstrating the efficiency of the green roof.